Curcumin‐loaded Pluronic® F‐127 Micelles as a Drug Delivery System for Curcumin‐mediated Photodynamic Therapy for Oral Application. (17th May 2021) - Dantas Lopes dos Santos, Diego; Besegato, João Felipe; de Melo, Priscila Borges Gobbo; Oshiro Junior, João Augusto; Chorilli, Marlus; Deng, Dongmei; Bagnato, Vanderlei Salvador; Rastelli, Alessandra Nara de Souza
Abstract: Antimicrobial photodynamic therapy (aPDT) is promising for oral decontamination. Curcumin has been used as photosensitizer; however, the hydrophobic properties can negatively affect aPDT. This study evaluated the aPDT efficacy using Cur‐loaded Pluronic ® F‐127 micelles against Streptococcus mutans and Candida albicans biofilms. Micelles characterization was performed by zeta potential, dynamic light scattering, transmission electron microscopy, absorption and fluorescence spectroscopy. Cur concentrations, cell viability by CFU mL −1 and confocal microscopy were determined. Data were analyzed by parametric and nonparametric tests under 5%. Cur‐loaded Pluronic ® F‐127 exhibited spherical shape, suitable particle size (≤100 nm), adequate polydispersity index, best stability, lower photodegradation and autoaggregation compared to unloaded‐Cur. Both microorganisms were sensitive to Cur‐loaded Pluronic ® F‐127 micelles aPDT, with minimum inhibitory concentration (MIC) of 270 μm and 2.1093 μm for S. mutans and C. albicans suspended culture, respectively. Cur‐loaded Pluronic ® F‐127 aPDT exhibited antibacterial/antifungal effect against the biofilms (~3 log10 reduction; P  ≤ 0.05); however, similar to unloaded ( P  ≥ 0.05). Confocal images confirmed these results. Cur‐loaded Pluronic ® F‐127 micelles exhibited good photo‐chemical properties and may be a viable alternative to deliver Cur and to improve aPDT effect during the treatment of dental caries. Moreover, Pluronic ® micelles can enhance the solubility, stability, permeability and control the release of Cur. Abstract : Biofilm control is crucial to interrupt oral biofilm‐dependent diseases. In this way, antimicrobial photodynamic therapy (aPDT) employs the use of a light source, photosensitizer and oxygen to inactivate oral microorganisms. Curcumin is a naturally occurring photosensitizer; however, its hydrophobic properties, low water solubility, fast degradation and low oral bioavailability can negatively affect aPDT. Polymeric micelles can encapsulate and solubilize hydrophobic drugs, such as curcumin, enhancing the bioavailability. Our results showed that Cur‐loaded Pluronic ® F‐127 micelles present good chemical properties and exert antimicrobial effect against S .  mutans and C. albicans biofilms (~3 log10 reduction), encouraging its use for oral applications. ​